Pengaruh Pemberian Video Animasi terhadap Pengetahuan Siswa SMAN 1 Ciampel terkait Pentingnya Konsumsi Tablet Tambah Darah - Wulan Furnama; Harianti, Rini (Universitas Pahlawan Tuanku Tambusai, 2024)
Anemia is a condition of reduced hemoglobin levels in the body, more common in women and young women compared to men. Unfortunately, many sufferers are unaware of their condition. WHO determined that the normal hemoglobin level in adolescent girls is 12 g/dl. This study employed a quasi-experimental approach using a one-group pre-test-post-test design. This research included 40 pupils from class X SMAN 1 Ciampel who had anemia. The result of the study is that there is an influence or increase in knowledge of class X students of SMAN 1 Ciampel after nutrition education using animated video media.